Implementasi Pelayanan Pendidikan Bagi Anak Autis Di SLB C Santa Lusia Pematang Siantar (Jurnal Pendidikan Agama dan Teologi, 2023)
Education is a human right that everyone must have, without exception for children with special needs, especially children with autism. Usually the education that autistic children get is only in special schools (SLB), and the costs incurred for this education are not small but are much more expensive than the regular school system. The effect is that many autistic children cannot experience the world of education because of their parents' economic factors. This research summarizes several problems, namely "How is the implementation of educational services for children with autism at SLB C Santa Lucia Pematang Siantar? The research methodology used is a qualitative approach and then outlined in the descriptive method. Data collection was carried out by observation and direct interviews regarding the service activities carried out by SLB C Santa Lucia Pematang Siantar. Sources of information in this study amounted to 3 people, consisting of 3 men.